Mathematical model of the location channel of the contour of the adaptation of radioacoustic atmospheric sounding systems - Kartashov, A.V. (Radiotekhnika, 2024)
The system of radio acoustic sounding (RAS) of the atmosphere is used in the process of solving actual scientific and applied tasks to ensure flights of aircraft, weather forecasting, studying the atmosphere, etc. However, the effectiveness of the existing radio-acoustic means is insufficient and there are practical needs for developing more promising structures and algorithms that will be implemented during the construction of specific types of sounding stations. Among the existing limitations of radio acoustic sounding systems, the main one is the violation of the Bragg condition, which determines the ratio between the lengths of acoustic and electromagnetic waves. The article considers the method of adapting RAS systems by changing the frequency of the sounding radio signal in order to fulfill the Bragg condition as the emitted acoustic pulse signal moves along the sounding path. It is shown that to increase the efficiency of the frequency adaptation method, it is necessary to use an adequate mathematical model of the information location channel, which describes the main features of the scattering of radio waves on the acoustic wave parcel, in the control circuit of the frequency of the sounding radio signal. The mathematical model of the location channel is considered. The study of the main types of probing acoustic and electromagnetic signals was performed using scattering bodies in the spectral representation. It has been revealed that in the presence of the Bragg condition detuning, the spectrum of the radio signal scattered on the sound has an asymmetric shape, and this is the main reason for the appearance of systematic errors in the results of sound speed measurements. Eliminating the identified errors will improve the efficiency of the adaptation devices and the RAS system as a whole.